Comparison of frost damages in apple plantations cultivated with environmental friendly growing technology - Dremák, P. (International Journal of Horticultural Science, 2010)
The global changes in climate and meteorological conditions have many negative consequences, which may diminished with adequate measures. In our continental climate, the winter frosts but also the late spring frosts are always threatening. There are technologies to avoid late frost damages (with spray irrigation or with smoking), but against winter minima, we are nearly helpless. The different damages experienced recently called our attention on the question of optimal condition, which is a delicate balance between the vegetative activity and the provision of nutrients. The excesses on both ends are increasing the danger of damages (Zatykó, 1980). Our examination was performed in the plantation, which was cultivated according to ecological and integrated technologies. The variable condition of the trees gave opportunity to evaluate the effects of cold temperatures as frost damages. Our results will represent not only the differences between varieties but also the effects of the growing technologies – which influence the condition of the plants – consequently, the measure of frost damages.